Disaster Radio for Communication of Vital Messages and Health-Related Information: Experiences From the Haiyan Typhoon, the Philippines. (4th March 2016) - Hugelius, Karin; Gifford, Mervyn; Örtenwall, Per; Adolfsson, Annsofie
Abstract: Objective: Crisis communication is seen as an integrated and essential part of disaster management measures. After Typhoon Haiyan (Yolanda) in the Philippines 2013, radio was used to broadcast information to the affected community. The aim of this study was to describe how disaster radio was used to communicate vital messages and health-related information to the public in one affected region after Typhoon Haiyan. Methods: Mixed-methods analysis using qualitative content analysis and descriptive statistics was used to analyze 2587 logged radio log files. Results: Radio was used to give general information and to demonstrate the capability of officials to manage the situation, to encourage, to promote recovery and foster a sense of hope, and to give practical advice and encourage self-activity. The content and focus of the messages changed over time. Encouraging messages were the most frequently broadcast messages. Health-related messages were a minor part of all information broadcast and gaps in the broadcast over time were found. Conclusion: Disaster radio can serve as a transmitter of vital messages including health-related information and psychological support in disaster areas. The present study indicated the potential for increased use. The perception, impact, and use of disaster radio need to be further evaluated. ( Disaster Med Public Health Preparedness . 2016;10:591–597)